2017
DOI: 10.1177/1178224216688887
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Access to Palliative Care

Abstract: Despite significant advances in understanding the benefits of early integration of palliative care with disease management, many people living with a chronic life-threatening illness either do not receive any palliative care service or receive services only in the last phase of their illness. In this article, I explore some of the reasons for failure to provide palliative care services and recommend some strategies to overcome these barriers, emphasizing the importance of describing palliative care accurately.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
209
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(243 citation statements)
references
References 12 publications
2
209
0
9
Order By: Relevance
“…to show a pattern that resembles the pattern seen in people dying of organ failure and frailty 14 . As the population ages and cancer survivors live longer with cancer, non-cancer comorbidities will increasingly have to be considered.…”
Section: Aging and Cancer Survivors With Non-cancer Causes Of Deathmentioning
confidence: 83%
See 1 more Smart Citation
“…to show a pattern that resembles the pattern seen in people dying of organ failure and frailty 14 . As the population ages and cancer survivors live longer with cancer, non-cancer comorbidities will increasingly have to be considered.…”
Section: Aging and Cancer Survivors With Non-cancer Causes Of Deathmentioning
confidence: 83%
“…A number of qualitative 7 and intervention or disease cohort studies, including randomized trials 8 , have been carried out, but we found no population-based studies that identify the individuals who are and are not using navigation. Furthermore, the need for navigation might be changing, given the accelerating discovery of innovative cancer treatments, the fact that more people are living longer with cancer 9 , the current focus on narrowing the gap between oncology and primary care 10,11 , the aging of the population, and greater interest in advance care planning and a palliative approach to care [12][13][14] . Population-based surveillance of people with life-limiting conditions can provide evidence that will help in critically appraising established navigation programs.…”
Section: Introductionmentioning
confidence: 99%
“…Palliative care focuses on 3 domains: management of patient symptoms; discussion of patient wishes, expectations and values via advance care planning and articulation of goals of care; and supporting families of those with life-limiting illness. 3 We expect the current SARS-CoV-2 pandemic to produce a surge of patients who present with acute respiratory failure due to pneumonia, including symptoms such as fever, dyspnea, respiratory congestion, pain, nausea and delirium. The risk of death is higher for older adults, particularly those with frailty and comorbidities.…”
Section: What Are the Challenges To Providing Palliative Care During mentioning
confidence: 99%
“…P alliative care (PC) is an approach to caring for individuals with life-threatening health conditions, with the focus being best quality of life (Hawley, 2017). It involves effective symptom management to address the physiological manifestations of diseases; interventions to promote the social, spiritual, and emotional well-being of patients and their families; and end-of-life (EOL) care to support patients' greatest comfort and dignity when death is imminent (World Health Organization, 2011; Worldwide Palliative Care Alliance [WPCA], 2014).…”
mentioning
confidence: 99%
“…It involves effective symptom management to address the physiological manifestations of diseases; interventions to promote the social, spiritual, and emotional well-being of patients and their families; and end-of-life (EOL) care to support patients' greatest comfort and dignity when death is imminent (World Health Organization, 2011; Worldwide Palliative Care Alliance [WPCA], 2014). Palliative care is recommended not only for cancer, but for any chronic life-threatening condition; for example, heart and kidney failure and various neurological diseases (Hawley, 2017). With the high prevalence and expected growth of chronic diseases not only in Canada, but worldwide, the need for PC is great now and will become even more so in the future (Canadian Hospice Palliative Care Association [CHPCA], 2014;Public Health Agency of Canada, 2016;WPCA, 2014).…”
mentioning
confidence: 99%